PROBLEMATICS OF LEARNING SCIENCE IN GRADE V ELEMENTARY SCHOOL STUDENTS IN MALANG CITY - Untari, Esti; Fany, Faiz Septia; Azizah, Maulidatul; Munawar, Muhammad Rofik; Rahmadini, Nova Anisha; Adellia, Regita Vio (Proceedings Series of Educational Studies, 2024)
Science learning in elementary schools experiences several fundamental problems. Based on exploration results, it was found that: 1) Learning media are varied but not well utilized by teachers. 2) The application of various learning models, such as cooperative models, project-based learning models, SAVI (Somatic, Auditory, Visual, Intellectual), and other learning models is not yet optimal. 3) The selection of varied learning methods, but teachers are still unable to practice them optimally. 4) Facilities such as science laboratories are not yet available. 5) Students' understanding of the concepts or materials explained is not deep, tending to cause misunderstandings. The purpose of this research is to increase motivation and make science learning more enjoyable.